Gestão democrática da educação: o pedagogo nas escolas municipais da Lapa – PR (2014-2017) - Veiga, Edicléa (2018)
This study has the theme of Democratic Management and the Pedagogical Work Organization, as a starting point of research were used the municipal schools of Lapa - PR. It is linked to the Postgraduate Program in Education of the Tuiuti University of Paraná, on bases of Public Policies and Education Management. Based on the reflections on the theme, it was defined as a research problem: School Democratic Management and was established as the guiding principle of educational systems and schools by the Federal Constitution of 1988 and regulated by the Law of Directives and Bases 9394/96 (BRAZIL, 1996), PNE 2014 -2024 (BRAZIL, 2014) and the Municipal Education Plan of the City of Lapa - PR (LAPA, 2015). Beginning on the legal regulations, it should be ask: What are the actions adopted by the pedagogues of the municipal schools of Lapa - PR in the organization of the pedagogical work starting from the perspective of democratic school management? The general objective of the research is to understand the pedagogue's action in the organization of pedagogical work in the perspective of democratic management in the municipal schools of Lapa - PR. The specific objectives may be presented: Conceptualize democratic management of education; To investigate the work of the pedagogue as a democratic manager in the school environment; Understand how these subjects organize work within the perspective of democratic management; To analyze the action of the pedagogue in the organization of pedagogical work in five municipal schools in the city of Lapa - PR; The research is justified by the need to understand the processes aimed at the organization of pedagogical work in the perspective of democratic management, thinking how they are articulated in the search for improvement in the work of the pedagogue as well as in the coexistence of those involved in the teaching-learning process. In order to analyze this theme, some authors will be needed. Almeida (2012), Brzezinski (2003) Cury (2002, 2005), Evangelista (2005), Ferreira (1999, 2000, 2002, 2004, 2007, 2012, 2013, 2017) (2004), Grinspum (2001), Kuenzer (2002) Gatti (2008, 2009, 2011), Libano (1990, 2001, 2002, 2004, 2006), Lima (2008), Luck 2000, 2001, 2008), Saviani (1991, 1996, 1977, 2008), among others. For methodology, it used documentary analysis and the technical data collection from interviews, enabling the in-depth study of the five municipal schools of Lapa- PR randomly chosen to develop the research. Thus, this work is of great relevance to broaden and stimulate the interaction between managers, teachers, school staff and community, aiming at a school that encompasses a broad and meaningful knowledge for students.